من جبل نفوسة وزوارة إلى أفق التواصل: دور العلماء في تعزيز الفهم بين ثقافتي المشرق والمغرب - براك, خضرة; بوخريص, حدة أزهار (Sharwes Scientific Journal, 2024)
The study delves into the influential role of civilizational relations between regions and peoples in shaping the course of history and culture. Exploration journeys serve as an effective means of transferring understanding and knowledge among societies, with prominent figures such as scholars and intellectuals playing a pivotal role. This research specifically focuses on exploring the impact of an exploratory journey highlighting the role of scholars and intellectuals from Nafusa mountain and Zuwara, and how this experience has contributed to enhancing civilizational communication between the East and the West. The research addresses the positive interaction revealed by the study's findings through the opinions of 102 professors, shedding light on the significance of academic research in enhancing this cultural interaction. Additionally, the study explores the increasing interest in the historical and cultural aspects of the journey, emphasizing the necessity of preserving cultural heritage and promoting effective communication among scholars. Top of FormIn this context, the study provides practical recommendations to enhance cultural exchange and activate academic links between institutions in the East and the West.